Real Estate Principle - Harwood; M Bruce (American : Prentice Hall, 1977)
Contents
1Introduction to Real estate
2. Nature and description of real eastate
3. Right and interests in land
4. Form of ownership
5. Transferring title
6. Recodation, abstracts, and title insurance
7. Contrac law
8. Real estate sales contracts
9. Mortgage theory and law
10. Trust dees
11. Mortgage lending
12. Morgage landers and alternatives
13. Taxes and assessments
14. Title closing and escrow..............
Keywords: Real estate principles; Real Estate Investment